LÜBNAN'IN TARiHSEL DOKUSU VE YÖNETiM ANLAYlŞlNDAKi MEZHEBi ETKiLER - Baglıoglu, Ahmet (Fırat University, 2008)
The Political system in Lebanon has been shaped according to relgion and sect foundation, and the counsil is set up as 5 cristians and fıve moslems. According to the pact of Taif in 1989 the number of chairs in the parliament became equal. Every sect's repç~sentative became available in the counsil and cabinent. As the religion and sects hae been based on political structure in Lebenon, equality and justice principals haven't been established among the people living in the country. The system founded according to the sects' principals has always been an obstacle for stabilization in Lebenon. Lebenon is a country where there are seventeen different ethnic groups and sects. A !of of political parties be ing available in i ts because of the religion and fact rather they belong to rather than the policy. The central administration in Lebenon couldn't set up a strong armybecause of conflicts among the sects and their leaders and the central administration has always been weak. Evry sect's and political group's establishing its militari forces has blown in inner war.
The Seetarian Factors in the Historial Structure and Perceptiveness of Administration of Lebanon
Keywords: Religious Studies; Din Araştırmaları